Extracellular ATP Limits Homeostatic T Cell Migration Within Lymph Nodes - Kobayashi, Daichi; Sugiura, Yuki; Umemoto, Eiji; Takeda, Akira; Ueta, Hisashi; Hayasaka, Haruko; Matsuzaki, Shinsuke; Katakai, Tomoya; Suematsu, Makoto; Hamachi, Itaru; Yegutkin, Gennady G.; Salmi, Marko; et al. (Frontiers in Immunology, 2021)
Whereas adenosine 5'-triphosphate (ATP) is the major energy source in cells, extracellular ATP (eATP) released from activated/damaged cells is widely thought to represent a potent damage-associated molecular pattern that promotes inflammatory responses. Here, we provide suggestive evidence that eATP is constitutively produced in the uninflamed lymph node (LN) paracortex by naïve T cells responding to C-C chemokine receptor type 7 (CCR7) ligand chemokines. Consistently, eATP was markedly reduced in naïve T cell-depleted LNs, including those of nude mice, CCR7-deficient mice, and mice subjected to the interruption of the afferent lymphatics in local LNs. Stimulation with a CCR7 ligand chemokine, CCL19, induced ATP release from LN cells, which inhibited CCR7-dependent lymphocyte migration in vitro by a mechanism dependent on the purinoreceptor P2X7 (P2X7R), and P2X7R inhibition enhanced T cell retention in LNs in vivo. These results collectively indicate that paracortical eATP is produced by naïve T cells in response to constitutively expressed chemokines, and that eATP negatively regulates CCR7-mediated lymphocyte migration within LNs via a specific subtype of ATP receptor, demonstrating its fine-tuning role in homeostatic cell migration within LNs.